Fat-free writing : business writing for the information age - Andrus, Carol (Crisp Pub. Menlo ParkUS, 2002)
Recommends several strategies for improving the clarity of written business communication including: using shorter words, sentences and paragraphs; avoiding cliches and redundancies; and using appropriate transitions and parallel structures. Advocates using active, specific verbs to add power to prose. Advises on formatting for reader-friendliness; provides a punctuation update, proofreading tips, and a how-to for incorporating numbers in writing.